2017
DOI: 10.25046/aj020356
|View full text |Cite
|
Sign up to set email alerts
|

Principal Component Analysis Application on Flavonoids Characterization

Abstract: Flavonoid is one of the bioactive compounds that are currently used in pharmaceutical and medicinal industries due to their health benefit. The focus of current research is mainly on the extraction and isolation of bioactive compounds; however non to date has explored on the identification of flavonoids classes under the Fourier Transform Infrared spectroscopy (FTIR). This gap presents an opportunity for the application of statistical analysis which can identify the distinct wavenumbers range of flavone, flava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In PCA analysis, the samples that seemed alike usually are group together while those far to each other indicate their differences. This pattern of analysis provides clear discrimination between samples as a tool of identification (Noh et al, 2017). From the PCA results obtained, it was observed that the five samples were linearly correlated as shown in Table 2 with the correlation coefficient values been in the range of +0.8065 to +0.9513, hence the suitability of subjecting the samples to PC analysis.…”
Section: Ftir Analysismentioning
confidence: 81%
“…In PCA analysis, the samples that seemed alike usually are group together while those far to each other indicate their differences. This pattern of analysis provides clear discrimination between samples as a tool of identification (Noh et al, 2017). From the PCA results obtained, it was observed that the five samples were linearly correlated as shown in Table 2 with the correlation coefficient values been in the range of +0.8065 to +0.9513, hence the suitability of subjecting the samples to PC analysis.…”
Section: Ftir Analysismentioning
confidence: 81%
“…As respects the PVA film loaded with Verbena officinalis extract (PVA-VE), the band of ν(O-H) stretch vibration attributed to phenols compounds such as phenols acids (protocatechuic, chlorogenic and vanillic) or verbascoside shifted to 3319 cm −1 [ 57 ]. Peaks of different heights are situated at 2920 cm −1 and 2851 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis highlighted the common wavenumber for carbonyl structure ν(C=O) bonds at 1732 cm −1 from the flavonoid structure such as luteolin, while the stretching vibration ν(C=C) was found at 1631 cm −1 , respectively, and the stretching vibration ν(C-O) bond shifted to 1086 cm −1 from the iridoids structure [ 50 ]. Additionally, the bending vibration of δ(C-H) was situated to lower wavenumbers at 948 cm −1 [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The spectral band located at 2979 cm −1 could be attributed to C-H stretching vibrations and to the solvent (ethanol), being due to the stretching vibrations of the O-H groups [63,70]. The spectral band of medium intensity located at 1641 cm −1 can be associated with the aromatic C=C stretching vibrations present in the condensed tannins [63], as well as C=O stretching vibrations and the presence of unsaturated bonds in flavonoid structures [69,71,72]; the presence of this peak suggests the presence of both flavones and flavanones [72]. The low intensity bands from 1453 and 1385 cm −1 can be related with C-H bending vibrations of the CH 2 and CH 3 groups [71], C=C-C stretching vibrations due to the aromatic ring [73], bending vibrations associated with aromatic cycles (flavonoids) [74], and O-H in plane deformation vibrations from polyphenolic compounds [73].…”
Section: Spectral Properties Of Vitis Vinifera L Red Grapes Hydroalcoholic Extractsmentioning
confidence: 98%